Predictors of deterioration of glucose tolerance and effects of lifestyle intervention aimed at reducing visceral fat in normal glucose tolerance subjects with abdominal obesity - Akita, Etsuko F (Blackwell Publishing Ltd, 2010)
Aims/Introduction:  The aim of the present study was to determine the predictors of deterioration of glucose tolerance in individuals with normal glucose tolerance (NGT) and abdominal obesity, and whether a lifestyle intervention to reduce visceral fat is effective in these individuals. Materials and Methods:  The study subjects were 251 individuals who had abdominal obesity with certain risk factors (hypertension, high fasting plasma glucose (FPG), elevated hemoglobin A(1c) (HbA(1c)), dyslipidemia and hyperuricemia) and underwent oral glucose tolerance test (OGTT) in 2004 and 2005. Results:  Using the area under the receiver operating characteristic curve, we found that PG at 0 min, 60 min, and area under the curve (AUC) of glucose from 0 to 120 min (AUC [glucose(0–120)]) in OGTT were significant predictors of deterioration of glucose tolerance, with optimal cut‐off values of 95 mg/dL, 158 mg/dL and 271 mg h/dL, respectively. Although the rate of deterioration of glucose tolerance didn’t decrease with reductions in visceral fat area (VFA) over the 1‐year period in subjects with NGT, the rate tended to decrease with reductions in VFA in high‐risk NGT subjects (PG at 0 min > 95 or at 60 min > 158, or AUC [glucose(0–120)] > 271). Conclusions:  These results suggest that reduction of visceral fat over 1 year might not be beneficial in all subjects with NGT, but is beneficial in high‐risk NGT. We propose that individuals with values of the aforementioned predictors higher than the cut‐off levels, even those with NGT, should receive a lifestyle intervention program aimed at reducing visceral fat to prevent deterioration of glucose tolerance. (J Diabetes Invest, doi: 10.1111/j.2040‐1124.2010.00080.x, 2011)